The big disconnect : the story of technology and loneliness - Slade, Giles (Prometheus Books, 2012)
Tablets, smart phones, and social networks all promise better opportunities to connect and stay connected. Yet what they really do is replace face-to-face interactions and disguise our growing inability to trust others. According to recent surveys, sixty million Americans, 20 percent of the population, feel sufficiently isolated to report that loneliness is a major source of unhappiness. In a sweeping overview that ranges from the late nineteenth century to the present, the author reveals how consumer technologies changed from analgesic devices that ameliorated the loneliness of a newly urban generation in the Gilded Age to prosthetic machines that act as substitutes for companionship in contemporary America. In a final investigative section, he describes ways in which some people are bucking the trend by consciously including interpersonal strategies that build empathy, community, and mutual acceptance. This interdisciplinary synthesis provides many insights into our increasingly artificial relationships and a vision of how we can rediscover genuine community and human empathy.